Shifting Boundaries of Marketing Management in E-Commerce: A Study through TAM (Technology Acceptance Model) - Manna, Yahya (European Journal of Sustainable Development, 2024)
This research tries to investigate the adoption of information technology and its constituents by the customers while making decisions to buy any product from the market utilising TAM. Many political and business related changes are being made in the context of marketing management. In the past 20 years, every domain of management has seen a transformation. Text explosion and information, information, technology and advancement in transport and communication revolutionised every domain of management marketing management which was regarded as the cost for the management is now regarded and recognised at the strategic level. The marketing managers are now enjoying high status in the corporate world. Traditionally, the field of marketing management was dependent on mass media and broadcast media, but with the advent of social media and the access of Internet to almost more than 50% of the consumers in every industry has transformed the field of marketing management. This change was recognised by many authors and researchers around the globe and there is a need to research from customers perspective that how easily consumers are adopting technology in decision making, For the assessment Technology Acceptance Model (TAM) was utilised. The data was collected from (n=138) marketing managers, the data was analysed by the use of SPSS 22.0 for descriptive analysis and for regression analysis and structural modelling method was applied. The finding suggest the technology acceptance model is highly applicable to marketing activities and some of its constituents rank high when it comes to make a decision to buy any product by the customer. However Attitude of using does not have any direct impact on Intention to use. Keywords: Marketing Managers, Status of Marketing managers, SEM, Lisrel 9.0., information technology, marketing activities.